2013
DOI: 10.1002/jbm.a.34782
|View full text |Cite
|
Sign up to set email alerts
|

In vivo response to an implanted shape memory polyurethane foam in a porcine aneurysm model

Abstract: Cerebral aneurysms treated by traditional endovascular methods using platinum coils have a tendency to be unstable, either due to chronic inflammation, compaction of coils, or growth of the aneurysm. We propose to use alternate filling methods for the treatment of intracranial aneurysms using polyurethane based shape memory polymer (SMP) foams. SMP polyurethane foams were surgically implanted in a porcine aneurysm model to determine biocompatibility, localized thrombogenicity, and their ability to serve as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(139 citation statements)
references
References 30 publications
2
136
0
Order By: Relevance
“…Previous work by Rodriguez et al with these materials (HH60 composition) included the implantation and histopathological evaluation after 0, 30, and 90 days in porcine aneurysms [38]. The SMPs were incubated in enzyme baths of pancreatin, collagenase and trypsin (initially tested with control SMPs to determine no degradation would occur to the polymer, only to the tissue) in order to remove tissue using a modified version of Zhang’s tissue removal protocol [39].…”
Section: Methodsmentioning
confidence: 99%
“…Previous work by Rodriguez et al with these materials (HH60 composition) included the implantation and histopathological evaluation after 0, 30, and 90 days in porcine aneurysms [38]. The SMPs were incubated in enzyme baths of pancreatin, collagenase and trypsin (initially tested with control SMPs to determine no degradation would occur to the polymer, only to the tissue) in order to remove tissue using a modified version of Zhang’s tissue removal protocol [39].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, their unique shape memory properties enable their catheter delivery through tortuous vasculature to the desired treatment site, where they expand to fill the site and promote clotting. Overall, these results combined with the positive prior in vivo study results indicate that the SMP foams present minimal risks from particulate release that may result in unintended downstream emboli formation and have high potential for use as effective and safe embolization devices [4,5,16,28].…”
Section: Discussionmentioning
confidence: 56%
“…However, due to an increase in the use of sophisticated imaging technology, prerupture aneurysm detection rates are rising [3]. Porous, low density shape memory polymer (SMP) foam is reported to be an effective aneurysm occlusion material with excellent biocompatibility as seen in a porcine model wherein rapid, stable thrombus formation and high volume occlusion was observed [4,5]. SMP foams are materials capable of maintaining a temporary shape and, upon application of a thermal, chemical, or optical stimulus, recovering their primary shape [6].…”
Section: Introductionmentioning
confidence: 99%
“…Singhal et al (2012) have demonstrated ultra-low density SMP foams with up to 70× volume expansion, 97–98% shape recovery after multiple cycles, and sharp, tailorable transition temperatures between 45–70 °C. In addition, the foams have shown excellent biocompatibility in vitro and in vivo , exhibiting the recruitment of collagen and connective tissue to form stable scar tissue, as well as clot formation within two minutes (Rodriguez et al, 2014a, 2014b, 2012; Singhal et al, 2012). …”
Section: Introductionmentioning
confidence: 99%